Range imaging observations of PMSE using the EISCAT VHF radar: Phase calibration and first results - Fernandez, J. R.; Palmer, R. D.; Chilson, P. B.; Häggström, I.; Rietveld, M. T. (HAL CCSD, 2005)
International audience A novel phase calibration technique for use with the multiple-frequency Range IMaging (RIM) technique is introduced based on genetic algorithms. The method is used on data collected with the European Incoherent SCATter (EISCAT) VHF radar during a 2002 experiment with the goal of characterizing the vertical structure of Polar Mesosphere Summer Echoes (PMSE) over northern Norway. For typical Doppler measurements, the initial phases of the transmitter and receiver are not required to be the same. The EISCAT receiver systems exploit this fact, allowing a multi-static configuration. However, the RIM method relies on the small phase differences between closely spaced frequencies. As a result, the high-resolution images produced by the RIM method can be significantly degraded if not properly calibrated. Using an enhanced numerical radar simulator, in which data from multiple sampling volumes are simultaneously generated, the proposed calibration method is validated. Subsequently, the method is applied to preliminary data from the EISCAT radar, providing first results of RIM images of PMSE. Data using conventional analysis techniques, and confirmed by RIM, reveal an often-observed double-layer structure with higher stability in the lower layer. Moreover, vertical velocity oscillations exhibit a clear correlation with the apparent motion of the layers shown in the echo power plots.